PENAKSIR PRODUK YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK BERSTRATA MENGGUNAKAN BEBERAPA PARAMETER - Icha Yulia; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article is a review of the study conducted by Kadilar [Journal of Statistical Planning and Inference, 139:2552-2558]. This article introduces three product estimators for the population mean in stratified random sampling using coefficient of variation, standard deviation, and coefficient of kurtosis. These estimators are biasedestimators. Then, the mean square errors of each estimator are compared for showing which one is the most efficient estimator. An example is given at the end of the discussion.